Teledentistry: An Art and Science of Healing - Rajan Shirolkar; Kosha Pritesh Ruparelia; Chandramani More; Pritesh Ruparelia (Wolters Kluwer Medknow Publications, 2011)
Teledentistry is a relatively new field that combines telecommunication technology and dental care. Teledentistry's roots lie in telemedicine. Telemedicine (and by inclusion teledentistry) has been defined as "the practice of health care delivery, diagnosis, consultation, treatment and education using interactive audio, video or data communications'. Improvement in accessibility of health care and lowered health care costs are only two of the many advantages that will emerge as teledentistry becomes integrated with, and fundamentally change, the practice of dentistry. Some barriers still exist for teledentistry practice, including legal, educational and insurance issues. In spite of having these "teething troubles", the potential of telemedicine and teledentistry is tremendous. In this article, we review the development of teledentistry, its use in dental education and treatment planning, its strengths and limitations, and its future role.